Visual Reaction Time in People with and without Diabetes - A Comparative Study - Pramanik, Tapas; Dhakal, R.; Pandit, R. (Nepal Medical College Journal, 2019)
Peripheral neuropathy is a common complication of type 2 diabetes in patients with poor diabetic control where reaction time increases in comparison to normal individual. Early detection of neural dysfunction denoted by increased reaction time will be helpful for the patient, to control blood sugar in order to avoid diabetic complications. This study was conducted to find out the neural deficit in diabetes by comparing the visual reaction time using ruler drop method between non-diabetics and diabetics and assessing the relationship of reaction time with increase in glycated hemoglobin (HbA1C) titre. It was a case control study among 38 diabetics and 31 healthy volunteers. Among the volunteers of age groups 20-39 years and 40-59 years, all patients with poor diabetic control showed significantly high reaction time in comparison to their non-diabetic counterparts (180.66 ms vs 231.11ms; 197.27ms vs 224.44 ms respectively). In age groups of 60-79 years, reaction time was also more in patients with high HbA1C in comparison to their non-diabetic counterparts (224.00 ms vs 230.90 ms). In comparison to non-diabetics, diabetics with increased HbA1C (7- 9%, 9-11%, 11-13%, >13%) all showed significantly higher reaction time (193.54 ms vs 219.00 ms; 193.54 ms vs 225.83 ms; 193.54 ms vs 236.66 ms and 193.54 ms vs more than 250 ms respectively). A positive Pearson Correlation (r = 0.4) was also noted between HbA1C (%) and reaction time (ms) amongst the patients with poor diabetic control. Damage of vasa nervosum and formation and accumulation of sorbitol and fructose in Schwann cells might disrupt structure and function of peripheral nerves leading to neuropathy and altered visual reaction time in diabetics.